Articulating Stakeholder: Production, Consumption and Sustainable Development - Zonin, Valdecir José (2011)
The paper presents a discussion of models of analysis for new patterns of production and consumption based on concepts related to sustainable development and its implications for groups, organizations and institutions involved in the context of a new institutional economics. These are changes of theoretical and practical approaches, guiding a multilinear and multidimensional transition process, involving sustainable development, sustainable consumption and a new institutional arrangement in a network, called stakeholder. The methodology reflects the context of a descriptive study, of hermeneutic character, with the construction of analytical schemes deriving from these interpretations. It is shown that sustainable development is possible through a sustainable consumption, a new institutional economics in the context of stakeholder. The analysis shows the inseparability and complementarity between changing patterns of production and consumption to a sustainable development perspective. The production and consumption need to address: the common good of humanity, a fair measure of intervention in nature, preserving the harmony of ecosystems and a solidarity consumption.